DA'WAH TASAWUF: CONCEPT AND IMPLEMENTATION IN BETAWI SOCIETY: DA'WAH TASAWUF: CONCEPT AND IMPLEMENTATION IN BETAWI SOCIETY - Solahuddin Abdul Rachman (Jurnal Syntax Transformation, 2023)
This dissertation aims to find out how far the role of the da'wah of Sufism in improving the quality of faith of the Indonesian people, especially the Betawi people. Where the Betawi people experience moral decadence, the erosion of identity associated with the decline in religious values. And with its geographical location, namely the Metropolitan City, the Betawi community is infected with a hedonistic and materialistic lifestyle. It is hoped that this da'wah of Sufism can fortify the ummah from moral depravity and become a means of fostering human relations with its Lord, and fellow communities around it, as well as forming believers with noble character who are loved by Allah and His Messenger. The method used in this study is to use the theory used in this research is to use the theory of the sociology of knowledge, while the approach is to da'wah-sufism in the Betawi community in Indonesia. The hypothesis to be achieved in the dissertation puts forward humanist da'wah thinking. The sociology of knowledge is a theory, while on the other hand the sociology of knowledge is a sociological-historical research method. As a theory, the sociology of knowledge takes two forms, namely: first, a purely empirical investigation through the exposure and structural analysis of how social interactions in fact influence thought. Second, epistemological research that focuses on how social relations and thought affect the issue of validity. In other words, as a theory for purely empirical inquiry, the sociology of knowledge examines the living forces and actual attitudes that underlie theoretical attitudes. Strength is not seen as a mere individual thing, but rather on the collective goals of a group that underlies individual thinking.